Protective role of Ferulic acid on acrylamide-induced testis toxicity in rats - Gezer, Arzu; Yakut, Seda; Kiliç Baygutalp, Nurcan; Tarakçi Gençer, Berrin (Ondokuz Mayis Universitesi, 2023)
It has become important over the last few years to reduce the detrimental effects of Acrylamide (ACR), which is a carcinogenic substance formed through the exposure of certain foods to high temperatures. The present investigation evaluated the defensive effect of ferulic acid (FA) against toxicity in testis tissue triggered by ACR in male rats. ACR (100 ppm) was administered orally in drinking water alone or with FA, for 30 days. This study revealed that treatment with FA could remarkably decrease MDA levels and significantly increase SOD levels in the testicular tissue of the ACR-treated rats. The intake of FA as a supplement is also supported by the increase in FSHR, LHR, and AR sex hormone receptor levels. FA also reduced the harmful effects leading to ACR by decreasing histopathological changes in the testicular tissue. This study demonstrates the probable protective mechanism of FA against testicular toxicity caused by ACR. © 2023 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: acrylamide; ferulic acid; rat; testis